Application possibilities of geo plastics in creating a comfortable urban environment (on the example of Kazan) - A. Rysaeva, Irina (2019)
Within the framework of this article, the authors, using the example of Kazan, considered the features of the manifestation of GEO plastics as a promising direction in the field of creating a comfortable urban environment. The concept and methods of GEOplast formation are identified in conjunction with the landscape components of the urban area. The authors proposed and reviewed the criteria for distinguishing GEO plastics according to the form of creation (horizontal, vertical) and seasonal characteristics (winter, summer), for the first time identified types of GEO plastics: natural-natural, natural-anthropogenic and cultural-artistic. The basis of the natural-natural type of GEO plastics is made up of objects of the protected zone and green areas, designed to perform environmental, recreational, aesthetic and artistic functions. The natural-anthropogenic type is differentiated by the authors into aquatic and relief geo-plastics, the basis of which form the unevenness of the relief of natural objects, as well as the introduction of elements of an artificial surface character into the natural environment. Finally, the cultural and artistic type of GEO plastics is based on the introduction into the natural environment of artificially created natural and artificial components and has as its goal the artistic education of citizens and the creation of the cultural appearance of the city. The authors found out that the largest number of them was located in the old central part of the city, on the left bank of the r. Kazanka, due to the history of the city, the accumulation of many tourist facilities here, the presence of historical symbols of the city. The work on the example of specific objects of Kazan showed the areas of application of GEO plastics, specifically for recultivation, solving engineering problems, improving the ecological situation, etc. As well as the authors gave some recommendations on creating a comfortable environment in urban landscapes using GEO plastics techniques.